Partisipasi Masyarakat Dalam Pengelolaan Sampah Di Bank Sampah Sakura Kelurahan Talang Kelapa Palembang - Budi Darmawan; Mulyanto Mulyanto; Didi Tahyudin (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2019)
The research, which is located in Talang Kelapa Sub-District, Palembang City, aims to determine community participation in waste management. The research method used is descriptive qualitative with a phenomenological approach. The results showed that community participation was divided four classifications, namely participation at the planning stage, participation at the implementation stage, participation at the benefit-taking stage, and participation at the evaluation stage. At the decision planning stage, the community attends meetings, proposes ideas, is willing to provide data and information, and participates in decision making. In the implementation phase, the community helps by the schedule of waste collection, provides solutions, and provides information. At the benefit-taking stage, the community will enjoy the benefits of the garbage bank and take care of the environment. At the evaluation stage, the community oversees the development of the garbage bank, as well as providing advice and criticism — factors that influence community participation due to economic benefits, skills and knowledge, and the environment. Community participation is also due to the invitation of friends or neighbours, and managers who are friendly and close to the community